Effectiveness of the combination of pelvic rocking and acupressure Sp 6 techniques with a combination of rebozo and counterpressure techniques on the duration of labor in the first stage in primiparous - Mujahidah, Sa'adah; Dewi, Anis Kumala; Rahayu, Hermeksi; Mayangsari, Dewi (CV LINK Education Publication, 2024)
Background: Women who are in labor for a long time can bleed because their uterus isn't working right, they are tired, or they are shocked. The baby may have a higher chance of suffocating badly, getting an infection, or getting hurt all at the same time. Acupressure, rebozo, pelvic rocking, and counterpressure can all change how long labor lasts. Objective: This study looked at how long stage I labor lasted for women who had never given birth before area when pelvic rocking, acupressure SP 6 techniques, rebozo, and counterpressure techniques were used together. Methods: This study uses a quantitative method with an experimental approach, especially a control group design with only a posttest. The sampling method was chosen by chance, and the sample size includes 12 interventions using a combination of pelvic rocking and acupressure SP6 and 12 interventions using a mixture of rebozo and counterpressure techniques. Using the Mann-Whitney test to look at the data. A partograph observation sheet is used in this study tool. Result: The pelvic rocking and acupressure techniques work less well than the rebozo and counterpressure techniques at shortening labor (ρ-value) by 0.326 units, which is more than 0.05. The mean rank for the rebozo technique and counterpressure is 13.88, while the mean rank for the pelvic rolling technique with acupressure SP six is 11.13 of them all. Conclusion: For the first few hours of labor, pelvic rocking along with SP6 works differently than rebozo and counterpressure. To speed up labor, pelvic rocking, acupressure at SP 6, the rebozo method, and counterpressure can be used.